Menstrual cycle, hormonal contraception and pregnancy in women's football: perceptions of players, coaches and managers - Forsyth, J. J.; Sams, L.; Blackett, A. D.; Ellis, N.; Abouna, M.-S. (Sport in society, 2023)
The perceptions of policies and research on menstrual cycle (MC), hormonal contraception (HC) and pregnancy of those involved in women's football from six European countries were analyzed via survey (n = 1127), and focus groups/interviews (49 women, 12 men). Thematically analyzed themes included 'support', 'player decisions', 'knowledge and understanding' and 'talking and discussion'. Support for MC, HC, pregnancy/childcare was felt to be dependent on the extent of knowledge and understanding, ease of communication between players and staff, and top-level intervention, such as policy, money and resources, which, regarding pregnancy, informed player decisions on whether they started a family. Support also came in the form of MC tracking and solidarity from teammates. To improve the women's game beyond policy on welfare, suggestions were to hire more women coaches and to formalize coach education to include research on MC, HC and pregnancy, which hopefully should incite open dialogue between the coach and athlete.